Social democracy and concertation. The Friedrich Ebert Foundation in the debate on the transition to democracy in Chile - Garategaray, Martina (Revista de Historia Social y de las Mentalidades, 2024)
This article examines Chile’s transition to democracy from an ideological and discursive perspective, focusing on the circulation of the concept of concertation among local politicians and intellectuals. It also highlights the notable but underexplored role of an international actor—the Friedrich Ebert Foundation (FES) of the German Social Democratic Party. From an intellectual and global history standpoint, the article first reconstructs the FES’s activities in Chile and then analyses the application of the concertation concept, initially formulated in Europe during the interwar period in dictatorial Chile in the 1980s. Throughout this process, the concept underwent various shifts and re-significations, which are particularly interesting for how they shaped the debate on democracy.
Keywords: Intellectual History; Transnational History; Circulation of Ideas; Friedrich Ebert Foundation; Democratic Transition